Place Matters: Memory, Community and Displacement in Oxnard’s Wagon Wheel Neighborhood - Garcia, Jacinta; Ruiz, Lorely; Estrada, Andrea; Issa, Sami; Gonzalez, Nayely; Lopez, Ana; Lopez, Claudia; Torres, Daniel; Garcia, Vicente; Salazar, Kyara; Camarena, Cinthia; Rodriguez, Yaqueline; et al. (CBR@CSUCI: An annual volume of community-based research, 2025)
EXECUTIVE SUMMARY Latino residents of Wagon Wheel Trailer Lodge were threatened with eviction in 2004 when their 169-space mobile home park and surrounding area was purchased by a land developer with plans to build new housing units and retail shops. Residents refused to move, so they organized a campaign for fair compensation and relocation rights and to be treated fairly by the developer and city officials. Residents secured the assistance of a local attorney to negotiate a fair settlement. After ten years of court battles and lobbying to the Oxnard City Council, residents of Wagon Wheel negotiated a settlement in summer 2014 that gave residents priority at the Wagon Wheel Family Apartments. This new housing complex included 120 units of affordable housing for low-income residents. Beyond a fair settlement, Wagon Wheel residents were interested in preserving the history of their tight-knit neighborhood. CSUCI students and Professor Alamillo conducted a community-based research (CBR) project to document the history of the Wagon Wheel Trailer Lodge community. For three semesters, students worked with members of the Wagon Wheel Residents Committee to document the stories of community unity, memories of struggle and resilience, discrimination, and displacement. It is important to recover the forgotten history Wagon Wheel residents to ensure that future working-class Latino/a neighborhoods are not easily displaced and erased from history.